Pendidikan Keberagamaan Berbasis Budaya Spiritual Di Kalangan Sai Study Group (SSG) - I Made Wirahadi Kusuma; I Made Pasek Subawa (Jayapangus Press, 2022)
Education is not only teaching that emphasizes on cognitive aspects, mastery of academic subjects, and not the development of the character of students towards the environmental reality which is religiously pluralistic. Therefore, although many educational institutions teach about the differences and respect for pluralism and comparative religion, it only comes to a cognitive understanding of each religion and does not know how to behave outside the religious discipline. It has big impact on humanitarian crises, not only at a concrete level in the form of physical culture, but also in non-physical forms which related to changes in attitudes, behavior and values ​​of life. The presence of the Sai Study Group Denpasar (SSGD) religious study group gave a new model to the pattern of religious education amidst the polarization of the development of religious study groups in Bali, especially in the formation of intellectual and character building. Religious education at SSGD contains acts of cognition, not just transfer of knowledge, verbalism, and education banking.